IDNLearn.com is your go-to resource for finding expert answers and community support. Join our interactive community and get comprehensive, reliable answers to all your questions.
Sagot :
To solve the equation [tex]\(\cot B = \sqrt{\frac{x+4}{x-4}}\)[/tex] for [tex]\(x\)[/tex], follow these steps:
1. Square both sides to eliminate the square root:
[tex]\[ \cot^2 B = \left(\sqrt{\frac{x+4}{x-4}}\right)^2 \][/tex]
Simplifying the right side, we get:
[tex]\[ \cot^2 B = \frac{x+4}{x-4} \][/tex]
2. Isolate the fraction involving [tex]\(x\)[/tex]:
[tex]\[ \cot^2 B = \frac{x+4}{x-4} \][/tex]
Multiply both sides by [tex]\(x-4\)[/tex] to get rid of the denominator:
[tex]\[ \cot^2 B \cdot (x - 4) = x + 4 \][/tex]
3. Distribute [tex]\(\cot^2 B\)[/tex] on the left side of the equation:
[tex]\[ \cot^2 B \cdot x - 4 \cot^2 B = x + 4 \][/tex]
4. Move all terms involving [tex]\(x\)[/tex] to one side and constants to the other:
[tex]\[ \cot^2 B \cdot x - x = 4 + 4 \cot^2 B \][/tex]
Factor [tex]\(x\)[/tex] out of the left side:
[tex]\[ x (\cot^2 B - 1) = 4 (1 + \cot^2 B) \][/tex]
5. Solve for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{4 (1 + \cot^2 B)}{\cot^2 B - 1} \][/tex]
Now, by using the trigonometric identity [tex]\(\cot^2 B + 1 = \csc^2 B\)[/tex], we get:
[tex]\[ 1 + \cot^2 B = \csc^2 B \][/tex]
Substituting this into our equation for [tex]\(x\)[/tex], we get:
[tex]\[ x = \frac{4 \csc^2 B}{\cot^2 B - 1} \][/tex]
Thus, the solution for [tex]\(x\)[/tex] in terms of [tex]\(B\)[/tex] is:
[tex]\[ x = \frac{4 \csc^2 B}{\cot^2 B - 1} \][/tex]
This is the value of [tex]\(x\)[/tex] that satisfies the given equation [tex]\(\cot B = \sqrt{\frac{x+4}{x-4}}\)[/tex].
1. Square both sides to eliminate the square root:
[tex]\[ \cot^2 B = \left(\sqrt{\frac{x+4}{x-4}}\right)^2 \][/tex]
Simplifying the right side, we get:
[tex]\[ \cot^2 B = \frac{x+4}{x-4} \][/tex]
2. Isolate the fraction involving [tex]\(x\)[/tex]:
[tex]\[ \cot^2 B = \frac{x+4}{x-4} \][/tex]
Multiply both sides by [tex]\(x-4\)[/tex] to get rid of the denominator:
[tex]\[ \cot^2 B \cdot (x - 4) = x + 4 \][/tex]
3. Distribute [tex]\(\cot^2 B\)[/tex] on the left side of the equation:
[tex]\[ \cot^2 B \cdot x - 4 \cot^2 B = x + 4 \][/tex]
4. Move all terms involving [tex]\(x\)[/tex] to one side and constants to the other:
[tex]\[ \cot^2 B \cdot x - x = 4 + 4 \cot^2 B \][/tex]
Factor [tex]\(x\)[/tex] out of the left side:
[tex]\[ x (\cot^2 B - 1) = 4 (1 + \cot^2 B) \][/tex]
5. Solve for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{4 (1 + \cot^2 B)}{\cot^2 B - 1} \][/tex]
Now, by using the trigonometric identity [tex]\(\cot^2 B + 1 = \csc^2 B\)[/tex], we get:
[tex]\[ 1 + \cot^2 B = \csc^2 B \][/tex]
Substituting this into our equation for [tex]\(x\)[/tex], we get:
[tex]\[ x = \frac{4 \csc^2 B}{\cot^2 B - 1} \][/tex]
Thus, the solution for [tex]\(x\)[/tex] in terms of [tex]\(B\)[/tex] is:
[tex]\[ x = \frac{4 \csc^2 B}{\cot^2 B - 1} \][/tex]
This is the value of [tex]\(x\)[/tex] that satisfies the given equation [tex]\(\cot B = \sqrt{\frac{x+4}{x-4}}\)[/tex].
Thank you for being part of this discussion. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. For precise answers, trust IDNLearn.com. Thank you for visiting, and we look forward to helping you again soon.